Проблеми та перспективи розвитку Індустрії 4.0 в Україні за умов євроінтегрування - Завербний, А. С.; Сало, К. Р.; Zaverbnyj, A. S.; Salo, K. R. (Видавництво Львівської політехніки, 2022)
Розглянуто поняття сутності “Індустрія 4.0” за умов євроінтегрування фахівцями. Досліджено проблеми, перспективи, загрози, можливості процесів формування, подальшого розвитку Індустрії 4.0 в Україні за умов євроінтегрування. Наведено структуру підходів щодо світового трактування поняття “Індустрія 4.0”. Проаналізовано ключові індикатори запровадження, розвитку Індустрії 4.0 в Україні. Досліджено потенційні можливості України до набуття статусу регіонального (східноєвропейського) лідера у сферах складних, наукоємних інженерних послуг за умов євроінтегрування.

Experts considered the concept of the essence of “Industry 4.0” under European integration conditions. The problems, prospects, threats, and possibilities of processes of formation and further development of Industry 4.0 in Ukraine under the conditions of European integration are studied. The structure of approaches to the global interpretation of the “Industry 4.0” concept is given. The main area of the latest achievements is closely related to information, communication, technical means, technologies, etc. They are the driving forces in the economy in the 21st century. It should be stated that information and communication tools and technologies have fundamentally changed, are changing, and are predicted to change almost everything. This applies both directly to business processes and to everyday life. Fundamental changes affect the methods of collecting, transmitting, analyzing, evaluating, storing, and managing information. The expediency of the transition of the Ukrainian economy to Industry 4.0 is determined by the following main drivers, which will indicate the possibility of integrating and improving the management systems of horizontal and vertical value chains, the introduction of digital technologies, the interconnection of goods and services (the so-called Internet of things (services), the introduction of the latest digital business models that will offer significant added value for consumers based on the development of individual solutions. The key indicators of the introduction and development of Industry 4.0 in Ukraine were analyzed. The potential opportunities of Ukraine to acquire the status of a regional (Eastern European) leader in the spheres of complex, knowledge-intensive engineering services under the conditions of European integration have been studied.
Problems and prospects of the development of industry 4.0 in Ukraine under the conditions of European integration
Keywords: Індустрія 4.0; інновації; цифровізація; розвиток; діджиталізація; технології; трансформування економіки; євроінтегрування; Industry 4.0; innovation; digitalization; development; digitalization; technologies; transformation of the economy; European integration; 004; 332.1; 338.1; 338.242; 338.36; 338.45; 339.9; 342.1; 65.01; 658.5